Coworking Space Di Pekanbaru Dengan Pendekatan Prinsip Arsitektur Organik Frank Lloyd Wright - Silmi Azula; Wahyu Hidayat; Yohannes Firzal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The high growth of start-ups in Pekanbaru has resulted in a growing need for office facilities that allows workers to be able to rent work facilities. However, the rental office are currentlyless efficient. This has become one of the difficulties, especially for new start ups. So coworking space is needed as a public space facility that can function as a container for work. Coworking space is workspace facility that is used together, shared and open by everyone. In building coworking space must also be able to share with the environment.Therefore, the selection of Frank Lloyd Wright's organic architectural principles was deemed appropriate for the design of coworking space buildings. The data collection methods usedare primary and secondary data. The result of this design is the design of coworking space Pekanbaru with the principle approach of Frank Lloyd Wright's Architecture. Using case studies with the same functions and themes, as well as the application of the principles of Frank Lloyd Wright's Architecture consisting of simplicity and calmness, design style,natural correlation, natural color, material properties, and spiritual integrity.Keywords: Coworking space, Frank Lloyd Wright, Organic